Sustainability, growth, and poverty alleviation: a policy and agroecological perspective - Vosti, Stephen A.; Reardon, Thomas (International Food Policy Research Institute, 1997)
Much more must be learned about the links among agricultural growth, poverty alleviation, and the sustainable use of natural resources, and the factors that condition these links. This report examines the complex issues associated with this critical triangle.